Working Toward a More Literate World: Reading Intervention Commentary. Issue 155 (March 2017) - Lovett, Maureen W.
Abstract: This issue of New Directions for Child and Adolescent Development summarizes recent and ongoing work to establish evidence‐based practices in early reading instruction and intervention and to improve access to and quality of literacy programs in low‐ and middle‐income countries. The authors describe projects of varying sizes and goals, conducted in multiple sites in Africa, the Middle East, Asia, and Latin America. What is immediately striking is the commitment to documenting the efficacy and effectiveness of these programs using wherever possible the methodological standards of intervention science and education research. Often thousands of children and hundreds of schools have been included despite the challenges involved. Data from these projects have informed plans for future programming in these countries, and results from large scale‐ups have provided insight into the most important factors necessary for scale‐up and sustainability. In this article, I present, in the context of an overview of the sum of these articles, my own thoughts on their importance and implications.